Advancement of platelet-inspired nanomedicine. (3rd October 2018) - Wang, Shujun; Yuan, Jun; Yang, Jie; Li, Na; Liu, Ran; Luan, Jianfeng; Ye, Dong
Abstract: Human platelets play important roles in several physiologic and pathologic processes. Any defects in platelet number and function can lead to a variety of bleeding complications; platelet transfusions are commonly used to improve platelet count and hemostatic function in these cases. However, transfusions are complicated by the short storage life of donated platelets and contamination risks. Synthetic platelet substitutes can render efficient hemostasis while allowing advantages of large-scale preparation, minimum contamination risk via effective sterilization, longer shelf-life, no need for blood type matching, and reduced risks of biologic or pathologic side effects. Recent efforts in synthetic platelet design have additionally focused on applications including hemostasis, drug delivery, and targeted delivery of cancer therapeutics. In the present review, we summarize the advancement of platelet-inspired nanomedicine for artificial blood component, tumor research, and treatment of thrombi.